THE RISE OF DIGITAL-PRENEURSHIP: A CASE STUDY ON THE ROLE OF SOCIAL MEDIA PLATFORMS IN EMPOWERING FEMALE-LED START-UPS - Wilson, Daniel; Li, Catherine; Garcia, Maria (Yayasan Adra Karima Hubbi, 2025)
The rise of digital-preneurship has revolutionized the entrepreneurial landscape, especially for women who face traditional barriers in business. Social media platforms, such as Instagram, Facebook, and TikTok, have emerged as key enablers for female entrepreneurs, offering low-cost solutions for brand development, customer engagement, and business growth. This study explores the role of social media in empowering female-led start-ups, with a focus on how these platforms provide opportunities to overcome gendered entrepreneurial challenges. The primary aim is to examine the strategies used by women entrepreneurs to leverage social media for business success. A qualitative case study design was employed, involving semi-structured interviews with 15 female entrepreneurs who use social media platforms as their primary business tool. Data were analyzed through thematic analysis, focusing on platform usage, content strategies, and entrepreneurial outcomes. The findings reveal that Instagram and TikTok are the most widely used platforms, with women entrepreneurs achieving higher engagement, brand visibility, and business growth through strategic use. Social media was found to significantly enhance business sustainability, customer loyalty, and market reach. This study concludes that social media platforms serve as vital empowerment tools for female entrepreneurs, enabling them to navigate traditional barriers and achieve scalable success. Future research should explore the long-term sustainability of these businesses and the specific challenges faced by women in digital entrepreneurship.